Logotherapy Sebagai Intervensi Keperawatan terhadap Psikologis pada Pasien Kanker - Romadiansyah, Zulfitrah; Wahyuni, Sri; Huda, Nurul (Journal of Telenursing (JOTING), 2024)
This study aims to determine and analyze logotherapy as a nursing intervention for the psychological condition of cancer patients. The method used is a systematic review obtained from various online databases from 2019-2024, namely Google Scholar, ScienceDirect, and Proquest with the English search keyword "Nursing Interventions AND Logotherapy AND Cancer Patients AND Chemotherapy" by using the guidelines from PRISMA 2020 and Joanna Briggs Institute (JBI). The research results showed that 10 articles met the inclusion criteria after screening the 605 articles identified. These studies state that logotherapy is a psychological nursing intervention implemented in cancer patients. In conclusion, research shows that logotherapy is effective in improving patients' psychological conditions, such as reducing anxiety about death, depression and reducing psychological pressure. Logotherapy is used as a non-pharmacological nursing intervention and can be integrated into holistic care for cancer patients undergoing chemotherapy. Keywords: Nursing Intervention, Cancer, Chemotherapy, Logotherapy